KOMPARASI PENURUNAN DAN WAKTU KONSOLIDASI ANATAR PVD POLA SEGIEMPAT DAN SEGITIGA BERBASIS PERHITUNGAN EMPIRIS DAN NUMERIS - Apriyani, Rani; Harnaeni, Senja Rum; Sunarjono, Sri; Solikin, Mochamad (Politeknik Negeri Semarang, 2024)
Infrastructure development in soft clay soil conditions will have an impact on the low bearing capacity of the soil and a decrease in the value of the soil's carrying capacity. Increasing the bearing capacity of the soil is carried out using PVD based on empirical and numerical calculations to produce settlement values and PVD consolidation times for rectangular and triangular patterns. In this research, the results obtained from empirical calculations are that the triangle pattern is the most appropriate pattern to be applied in this case because it has a fast consolidation time value for BH 04, 05, 06, respectively, only takes 125, 124, 128 days with large decline 0.00903, 0.9012, 0.85743. Meanwhile, in numerical calculations, the triangle pattern has a fast time for BH 04, 05, 06 respectively requiring 280, 190, 134 days with a decrease of 0.0112000, 0.0001781, 0.0000006.